If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 59 = 5y + -11 Reorder the terms: 59 = -11 + 5y Solving 59 = -11 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 59 + -5y = -11 + 5y + -5y Combine like terms: 5y + -5y = 0 59 + -5y = -11 + 0 59 + -5y = -11 Add '-59' to each side of the equation. 59 + -59 + -5y = -11 + -59 Combine like terms: 59 + -59 = 0 0 + -5y = -11 + -59 -5y = -11 + -59 Combine like terms: -11 + -59 = -70 -5y = -70 Divide each side by '-5'. y = 14 Simplifying y = 14
| 180=30+123+b | | 9=n+4 | | 2x+4+6X=-68 | | 9=2+4 | | 180=(16x-3)+45 | | 38=6x+6x-10 | | 29=6 | | -11=p-17 | | 4x-6+5x=57 | | 9=3g | | 180=16x-3+45 | | 5x+1-2x=27 | | 0.75y=2x-6 | | 2(y+2)-8=0 | | -4x^2+19x=-320 | | x+1-4x=13 | | 5/8q=-20 | | 8x-13y=12 | | Y-5=m(x-6)form | | -18=-x-11 | | 8y+y^2=180 | | 8y+y^2=189 | | 0.54(6)+.06x=.18(24+x) | | f(4)=9x+7 | | -8+6x+4x=-98 | | 13x+1=9x+5 | | 3(c-63)=27 | | 5x-9+3x=87 | | f(5)=3x+x^2 | | (X-2)/10=(x-7)/5 | | X+325=520 | | f(x)=3x+x^2 |